1993
DOI: 10.1159/000463228
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Reactions to Arthropods

Abstract: Allergic reactions to arthropods are some of the most important factors involved in the development of asthma and the precipitation of attacks. Although sensitization to arthropods occurs most frequently in atopic individuals, continual exposure induces parallel sensitivities in a high percentage of non-atopics. The allergens involved are numerous, and although there is a degree of cross-reactivity most arthropod groups exhibit specific allergens that may be of somatic or excremental origin. Prevention is larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…These species became serious pests, causing considerable loss and damage to stored goods of both animal and plant origin (Hinton, 1945;Burges, 1959;Kantack & Staples, 1969;Mroczkowski, 1975;Beal, 1991;Veer, Prasad & Rao, 1991a;Veer, Prasad & Rao, 1991b;Veer & Rao, 1995;Veer, Negi & Rao, 1996;Imura, 2003;Rajendran & Hajira Parveen, 2005;Lawrence & Slipinski, 2010) and to objects of organic origin in museums of cultural and natural history (Jurecka, Gebhart & Mainitz, 1987;Zaitseva, 1987;Armes, 1988;Bousquet, 1990;Pinniger & Harmon, 1999;Stengaard et al, 2012;Querner, 2015). The hastisetae released by the larva throughout its entire development and abandoned in the environment in association to the exuviae are an important contaminant in dwelling, public spaces as well as food stuff (Gorham, 1979;Gorham, 1989;Burgess, 1993) and can contribute as allergens in humans (Wiseman et al, 1959;Johansson, Wüthrich & Zortea-Caflisch, 1985;Baldo & Panzani, 1988;Burgess, 1993;Pauli & Bessot, 2009;Gorgojo et al, 2015;MacArthur et al, 2016): chitin, likely the main constituent of the hastisetae, is in fact a powerful and widely recognized allergen, and its interaction with Th2 lymphocytes and human chitinases enhances the inflammation process (Brinchmann et al, 2011;Bucolo et al, 2011;Mack et al, 2015). However, it is still unclear whether the inflammatory effect of the hastisetae is attributable to the mechanical action of the seta and its penetration through the epithelia or if it is associated to the presence of specific molecules capable to start an immunological reaction.…”
Section: Hastisetae and Human Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…These species became serious pests, causing considerable loss and damage to stored goods of both animal and plant origin (Hinton, 1945;Burges, 1959;Kantack & Staples, 1969;Mroczkowski, 1975;Beal, 1991;Veer, Prasad & Rao, 1991a;Veer, Prasad & Rao, 1991b;Veer & Rao, 1995;Veer, Negi & Rao, 1996;Imura, 2003;Rajendran & Hajira Parveen, 2005;Lawrence & Slipinski, 2010) and to objects of organic origin in museums of cultural and natural history (Jurecka, Gebhart & Mainitz, 1987;Zaitseva, 1987;Armes, 1988;Bousquet, 1990;Pinniger & Harmon, 1999;Stengaard et al, 2012;Querner, 2015). The hastisetae released by the larva throughout its entire development and abandoned in the environment in association to the exuviae are an important contaminant in dwelling, public spaces as well as food stuff (Gorham, 1979;Gorham, 1989;Burgess, 1993) and can contribute as allergens in humans (Wiseman et al, 1959;Johansson, Wüthrich & Zortea-Caflisch, 1985;Baldo & Panzani, 1988;Burgess, 1993;Pauli & Bessot, 2009;Gorgojo et al, 2015;MacArthur et al, 2016): chitin, likely the main constituent of the hastisetae, is in fact a powerful and widely recognized allergen, and its interaction with Th2 lymphocytes and human chitinases enhances the inflammation process (Brinchmann et al, 2011;Bucolo et al, 2011;Mack et al, 2015). However, it is still unclear whether the inflammatory effect of the hastisetae is attributable to the mechanical action of the seta and its penetration through the epithelia or if it is associated to the presence of specific molecules capable to start an immunological reaction.…”
Section: Hastisetae and Human Healthmentioning
confidence: 99%
“…Megatominae are also one of the arthropod groups most commonly recorded inside houses (Gamarra, Outerelo & Hernández, 2009;Bertone et al, 2016;Madden et al, 2016); the larvae persist in these environments for months, even for years, feeding on food (Gorham, 1979;Gorham, 1989;Hirao, 2000), pet food (Rudolph et al, 1981), dust, insect remains and clothes, especially wool fabric (Bouchet, Lavaud & Deschamps, 1996). This prolonged presence inside houses together with the persistence of the hastisetae in the environment greatly increase the possibility for the humans to come into contact and develop a sensitization to these detachable hairs (Wiseman et al, 1959;Ayres & Mihan, 1967;Kaufman, Bado & Tovey, 1986;Burgess, 1993;Jakubas-Zawalska et al, 2016). The direct exposure of hastisetae to the skin, maybe due to contaminated bed or clothes, causes severe dermatitis (Sheldon & Johnston, 1941;Cormia & Lewis, 1948;Okumura, 1967;Ahmed et al, 1981;Alexander, 1984;Johansson, Wüthrich & Zortea-Caflisch, 1985;Southcott, 1989;Horster et al, 2002;Zanca, Zanca & Cassisa, 2012;Hoverson et al, 2015;MacArthur et al, 2016), while the repeated inhalation over a longer period may cause asthma (Cuesta-Herranz et al, 1997;Brito et al, 2002;Bernstein et al, 2009).…”
Section: Hastisetae and Human Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…These species became serious pests, causing considerable loss and damage to stored goods of both animal and plant origin (Hinton, 1945;Burges, 1959;Kantack and Staples, 1969;Mroczkowski, 1975;Beal, 1991;Veer et al, 1991a, b;Veer and Rao, 1995;Veer et al, 1996;Imura, 2003;Rajendran and Hajira Parveen, 2003;Lawrence and Slipinski, 2010) and to objects of organic origin in museums of cultural and natural history (Jurecka, 1987;Zaitseva, 1987;Armes, 1988;Bousquet, 1990, Pinniger andHarmon, 1999;Stengaard Hansen et al, 2012;Quarner, 2015). The hastisetae released by the larva throughout its entire development and abandoned in the environment in association to the exuviae are an important contaminant in dwelling, public spaces as well as food stuff (Gorham, 1979;Burgess, 1993) and can contribute as allergens in humans (Wiseman et al, 1959;Johansson et al, 1985;Baldo and Panzani, 1988;Burgess, 1993;Gorgojo et al, 2015;McArthur et al, 2016) Manuscript to be reviewed main constituent of the hastisetae, is in fact a powerful and widely recognized allergen, and its interaction with Th2 lymphocytes and human chitinases enhances the inflammation process (Brinchmann et al, 2011;Bucolo et al, 2011;Mack et al, 2015). However, it is still unclear whether the inflammatory effect of the hastisetae is attributable to the mechanical action of the seta and its penetration through the epithelia or if it is associated to the presence of specific molecules capable to start an immunological reaction.…”
Section: Hastisetae and Human Healthmentioning
confidence: 99%
“…There is bron chial hyper-reactivity in asthma, and a consistent eleva tion in serum IgE levels [130]. Common allergens include skin fragments from house dust mites and other arthro pods [83,84,131]; animal dander, from pets or laboratory animals in an industrial context [82,132]; and fungi and moulds [88], particularly those found inside buildings [133], such as pénicillium [89,134].…”
Section: Asthma and Other Allergic Conditionsmentioning
confidence: 99%